PENGARUH DISIPLIN KERJA DAN BUDAYA KERJA TERHADAP KINERJA KARYAWAN PERUSAHAAN DAERAH AIR MINUM KOTA BENGKULU - Hermawati Hermawati (Creative Research Management Journal, 2020)
This study aims to determine the existence of the influence of work discipline and work culture on the performance of the employees of the Bengkulu City Water Supply Company. Methods of data analysis using multiple linear regression, multiple linear regression, coefficient of determination, t test and F test. This type of research is an explanative type of research in which obtaining information and field data is carried out by field surveys through direct observation using a questionnaire. The data used in this research is quantitative data in the form of data on the number of employees at the Regional Drinking Water Company in Bengkulu City and qualitative data in the form of the history of the establishment of a company being studied. While the data collection techniques in this study are primary and secondary data sources, in which primary data is in the form of questionnaires and observation, while secondary data is in the form of documentation and literature study and the sampling technique uses the census method by taking a sample of a number of existing populations.